Analisa Perbandingan Karakteristik Bodi dan Chassis pada Prototype Kendaraan Listrik - Dwinanto, Arya Yudistira; Muhammad, Fadhil Burhanuddin (Jurnal Rekayasa Mesin, 2015)
In the design of electric vehicles prototype, there are many things that must be taken into account and considered to be used completely without danger and failure in materials. In general, they are the design of body, chassis or frame design, the design of the transmission system, the design of the engine (motor), and the design of electrical installations. Vehicle chassis monocoque has a lighter weight compared to the vehicle chassis with a ladder. The weight of the vehicle has a considerable effect on the efficiency of the motor in which the motor work harder. Body vehicle glass fiber and carbon fiber also has a weight that is much different. With the same frame, the vehicle weight is obtained with a machine that utilizes carbon fiber body and fiber glass 43 kgf and 54 kgf. Excess carbon fiber monocoque chassis can be combined to produce the weight of the vehicle 36 kgf.